1998
DOI: 10.4141/p97-127
|View full text |Cite
|
Sign up to set email alerts
|

Effect of imazethapyr and imazamox soil residues on several vegetable crops grown in Ontario

Abstract: . Effect of imazethapyr and imazamox soil residues on several vegetable crops grown in Ontario. Can. J. Plant Sci. 78: 647-651. Use of imidazolinone herbicides has often resulted in carryover effects on sensitive rotational crops. The effect of soil residues of imazethapyr and imazamox on several vegetable crops grown in rotation with soybean (Glycine max [L.] Merr.) was investigated over a 5-yr period in southern Ontario. Imazethapyr at 0, 100 and 200 g a.i. ha -1 was applied preemergence to soybean from 1991… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 12 publications
(11 reference statements)
1
29
0
Order By: Relevance
“…30) In another study conducted in soils with a high pH (alkaline, cracking clay, pH 8.6) no residue was found in the top 10 cm of soil; however, 0.6-1.6 ng/g of imazethapyr was reported at 20-40 cm soil depths after four months of imazethapyr application. 21) O'Sullivan et al 21) demonstrated the marked effect of rainfall on imazethapyr persistence and concluded that the herbicide was lost from the profile either by leaching to below 40 cm or by microbial breakdown due to the wetter years' being more conducive to microbial activity in the topsoil. The bioassay results showed a marked effect of rainfall on residue persistence.…”
Section: Terminal Residues Of Imazethapyr In Soilmentioning
confidence: 99%
See 3 more Smart Citations
“…30) In another study conducted in soils with a high pH (alkaline, cracking clay, pH 8.6) no residue was found in the top 10 cm of soil; however, 0.6-1.6 ng/g of imazethapyr was reported at 20-40 cm soil depths after four months of imazethapyr application. 21) O'Sullivan et al 21) demonstrated the marked effect of rainfall on imazethapyr persistence and concluded that the herbicide was lost from the profile either by leaching to below 40 cm or by microbial breakdown due to the wetter years' being more conducive to microbial activity in the topsoil. The bioassay results showed a marked effect of rainfall on residue persistence.…”
Section: Terminal Residues Of Imazethapyr In Soilmentioning
confidence: 99%
“…A low concentration of imazethapyr in soil is also compensated for high microbial activity, which increases the rate of degradation. 6,8,30,[32][33][34][35][36] O'Sullivan et al 21) reported imazethapyr residues mainly in the top 0-10 cm soil fraction; however, some quantity of imazethapyr residue was found at 10-20 and 20-40 cm depths, also. Besides the organic matter, clay can also play an important role in the degradation of pesticides.…”
Section: Terminal Residues Of Imazethapyr In Soilmentioning
confidence: 99%
See 2 more Smart Citations
“…Injury of sensitive crops to herbicide residues that are grown 1 yr after herbicide application can result in yield reductions due to herbicide persistence (Curran et al 1996;Helling 2005). For example, several vegetable crop species are sensitive to residual commercial herbicides like imazethapyr (O'Sullivan et al 1998), mesotrione (Felix et al 2007), and saflufenacil (Robinson and McNaughton 2012). A related concern for which growers lack sufficient understanding is the effect of residues from herbicides applied in the previous year on cover crop growth and effectiveness.…”
mentioning
confidence: 99%